ANALYSIS OF HUMAN RESOURCES, MOTIVATION, AND ITS RELATIONSHIP WITH THE MANAGEMENT OF ENTERPRISE RESOURCE MANAGEMENT - wiwi cahyani (CV. Four Son Scholarship, 2023)
This study aims to determine the human resources, motivation and how it relates to the management process of enterprise resource management. The research method used is to use the literature study research method to analyze human resources, motivation and its relationship with the management of Resource Management in the company. In the process of finding information, researchers collect information from national journals, citations, books and theses related to the title of the study. The following are the stages of literature study in this research: a) define the study or the scope of the topic to be reviewed, B) identify reference materials relevant and quality through Google Scholar, c) selecting several references from Google Scholar and grouping files based on research needs, d) compiling a synthesis matrix of articles obtained, 5) writing a review, 6) concluding and applying the results of the review. The results showed that human resources and motivation have a close relationship with the stability of a company. Management Resource Management in the company is a system or method for moving and maintaining the stability of the company. Providing motivation will improve the quality of human resources. So, motivation and human resources are one unit in achieving good performance and quality